Masalah Kebijakan Sertifikasi Benih Dan Bibit Tanaman Hutan Di Jawa Barat (Penerapan Pendekatan Advocacy Coalition Framework) - Taofik Hidayat; Euis Dasipah; Dety Sukmawati; Zahra Nur Safa (OrchidAgri, 2023)
The purpose of this study is to obtain policy direction recommendations for seed source, seed and seedling certification in West Java using ACF (Advocacy Coalition Framework) approach and multiple linear regression. A key alignment of the two goals for the government is compliance with statutory or government-sponsored regulations, with the result that the stability of seed production is disrupted by suppliers. Analysis using the ACF framework has produced policy guidelines for mandatory certification of seed quality related to seed source, seed quality, and compliance with regulations issued by central governments. The objectives of the activity to certify seed sources, seed quality and seed quality in accordance with the P.3 policy were not optimally achieved. This is reflected in the prominence of those who are less active in certifying the forest products they produce.Merchant certification activity has a significant value of 0.023. Vendor certification activities are reduced due to the P.3 policy requiring local governments to have their own forest plant nurseries. Procurement and distribution agencies generally produce on a large scale when they receive